Effect of pH and heat treatment on structure, surface characteristics and emulsifying properties of purified camel β-casein. (15th December 2021) - Ellouze, Maroua; Vial, Christophe; Attia, Hamdi; Ayadi, Mohamed Ali
Graphical abstract: Highlights: Camel milk β-casein was compared to bovine β-casein in an oil–water low fat emulsion. Emulsifying activity at pH 9 was higher for camel than bovine β-caseins. Low adsorption of camel β-casein at pH 6 to oil droplets was due to micellar structure. Cameline β-caseins provided interesting emulsion properties than bovine at pH 3 and 9. Abstract: Oil-in-water emulsions (20%/80%, w/w) were stabilised by two types of β-caseins (1 g/L, w/w) extracted by rennet coagulation from camel and cow's milk, respectively. Both extracts were treated under different ranges of pH (3.0, 6.0 and 9.0) and temperature (25, 65 and 95 °C for 15 min) before emulsification. The emulsifying properties of the proteins were studied by surface and interfacial measurements. Results show that the emulsifying activity (EAI) of camel β-casein is higher than the bovine protein. Yet, both proteins exhibited heat stability and nonsignificant effect of temperature was reported. Conversely, a significant effect of pH on camel β-casein was recorded: at pH 6.0, the lowest values of EAI were measured and explained by the formation of micellar protein structure. Under such conditions, camel β-casein is therefore a novel emulsifying protein with high potential to stabilise oil-in-water interfaces which provides numerous applications for the food chemistry field.